Identifikasi Morfologi Tumbuhan Kantong Semar (Nepenthes Sp.) Sebagai Bahan Ajar Tumbuhan Tingkat Tinggi Di Kawasan Wisata Gunung Galunggung Kabupaten Tasikmalaya - Rinaldi Rizal Putra; Rita Fitriani (UNIVERSITAS PGRI MADIUN, 2018)
Mount Galunggung is one of the tourism icons in Tasikmalaya Regency which has highly potential of biodiversity, especially in various of plants. In addition to showing the natural tourism, Mount Galunggung is also a media for learning high-level plants for developing science in the university. One of the potential diversity of plants in Mount Galunggung is kantong semar, which is known with botanical name as Nepenthes sp. Nepenthes are known as tropical plants that can live and survive in extreme conditions with low nutrients. These plants are classified into carnivorous plants. This research was aimed to identify various species of Nepenthes in Tasikmalaya Regency based on morphological characters. This research was conducted in February until July 2018, located in Mount Galunggung Tasikmalaya Regency using descriptive and exploratory methods. Data collected were morphological identification of Nepenthes and environment conditions. Morphological identification was carried out by visual observation of organs in Nepenthes such as root, stem, leaf, pitcher, flower, fruit and seed that are expected to give preliminary data that can provide information to determine the classification. The result of this research concluded that only one species of Nepenthes was found in Mount Galunggung and that was included to Nepenthes gymnamphora.